2006
DOI: 10.1177/0142723706059447
|View full text |Cite
|
Sign up to set email alerts
|

Reference time in child English and Polish

Abstract: The purpose of this research was to investigate the manner in which reference time becomes integrated into the child's emerging systems of temporal reference. The longitudinal data from six children learning English and six children learning Polish were analyzed within the period from about 1;6 to 5;0. The temporal reference within an event time and a reference time system was evaluated. Regarding reference time constructions, we traced the acquisition of the following terms: (1) English, when, then, before, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…Children aged two to three years learn to use temporal adverbs, such as 'now' , 'already' , 'later' , 'when' , and 'soon' (Weist, 2014;Weist & Buczowska 1987;Weist & Zevenbergen, 2008). They will also use terms such as 'yesterday' and 'tomorrow' (Pawlak et al, 2006;Weist & Buczowska 1987), although not necessarily accurately. One important issue is whether this indicates that children are using these terms to single out points in time per se, rather than events.…”
Section: Stage (B): Event-based Time (2-3 Years)mentioning
confidence: 99%
“…Children aged two to three years learn to use temporal adverbs, such as 'now' , 'already' , 'later' , 'when' , and 'soon' (Weist, 2014;Weist & Buczowska 1987;Weist & Zevenbergen, 2008). They will also use terms such as 'yesterday' and 'tomorrow' (Pawlak et al, 2006;Weist & Buczowska 1987), although not necessarily accurately. One important issue is whether this indicates that children are using these terms to single out points in time per se, rather than events.…”
Section: Stage (B): Event-based Time (2-3 Years)mentioning
confidence: 99%
“…At this phase of development, children demonstrate the capacity to establish reference time at a remote location (i.e., away from speech time), and then, they relate the primary event in the utterance to the reference time interval. In order to capture this developmental process, Pawlak, Oehlrich, and Weist (2006) investigated the naturalistic observations of six children acquiring English and six children acquiring Polish in the age range from 1;6 to 5;0 (i.e., the same children who participated in Weist et al, 2004). The 2004 study focused on the ET system, and the 2006 study was focused on the emergence of the RT system.…”
Section: The Emerging Reference Time (Rt) Systemmentioning
confidence: 99%
“…The 2004 study focused on the ET system, and the 2006 study was focused on the emergence of the RT system. Pawlak et al (2006) traced the emergence of the seven terms shown in Table 2, and she derived the following two dependent measures: 1) the age on the initial correct occurrence of each target term (see Table 2), and 2) the age on the initial correct occurrence of three contrasting temporal constructions as follows: a) when / jak versus then / potem, b) before / przed versus after / po, and c) any two of the three deictic adverbs. Summing across the target terms for the 6 children acquiring one of the languages, the average age of the initial correct occurrence was 2;11 for English and 2;10 for Polish.…”
Section: The Emerging Reference Time (Rt) Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Young children do not yet know about the custom of recounting events in their usual script order of occurrence, nor do they clearly understand the meaning of temporal adverbs or calendric reference. Studies that have directly compared the acquisition of different systems of marking temporality report morphological means of temporal reference preceding the use of temporal adverbials in children's speech (e.g., Pawlak, Oehlrich, & Weist, 2006) with comprehension studies suggesting that 3‐year‐olds are able to distinguish minimal tense‐aspect morphological contrasts but not contrasts between lexical forms such as when/then, before/after (Weist, Atanassova, Wysocka, & Pawlak, 1999) and that 2‐year‐olds can differentiate past and present tense on the basis of the auxiliaries will and did , copula be , and progressive but are not aided by the inclusion of temporal adverbials (Valian, 2006). Older learners, however, as a result of their L1 experience, do know these things.…”
mentioning
confidence: 99%